2020
DOI: 10.1177/0198742920911183
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey on Mental Health Professional Development in Juvenile Justice Facilities: Implications for Youth Reentry

Abstract: A national study of clinical directors examined professional development (PD) focused on mental health provided to professionals in juvenile justice facilities for adjudicated youth. A total of 85 clinical directors responded to a mail survey (45% return rate). The survey questions related to (a) topics of staff training and the basis for choosing topics, (b) which professionals participated in each PD topic, (c) training format and frequency of PD, (d) recommended attributes of PD, (e) methods of eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Such inconsistencies also may influence the implementation of universal mental health interventions as part of the Tier 1 framework. For instance, a national survey on staff mental health training in juvenile facilities found that mental health directors received the most training, while teachers and frontline staff received the least (Gagnon & Swank, 2017). To improve Tier 1 implementation fidelity, researchers need to identify effective ways to train all staff in their adopted evidence-based mental health and trauma-related interventions.…”
Section: Implications For Researchersmentioning
confidence: 99%
“…Such inconsistencies also may influence the implementation of universal mental health interventions as part of the Tier 1 framework. For instance, a national survey on staff mental health training in juvenile facilities found that mental health directors received the most training, while teachers and frontline staff received the least (Gagnon & Swank, 2017). To improve Tier 1 implementation fidelity, researchers need to identify effective ways to train all staff in their adopted evidence-based mental health and trauma-related interventions.…”
Section: Implications For Researchersmentioning
confidence: 99%
“…Second, it may be that any inadequacies in training could impact the study results. In general, JCF education and correctional staff are rarely provided professional development related to mental health and when it is provided, it is often a single day and viewed as ineffective by participants (Gagnon & Swank, 2021). As such, staff may not have the knowledge-base to enact interventions if provided cursory training.…”
Section: Discussionmentioning
confidence: 99%
“…Working at JJFs can be stressful and demanding, and staff may experience a phenomenon called "Corrections Fatigue," which refers to a prolonged type of fatigue generated by facing the stressors in corrections for an extended period of time (James & Vanco, 2021). As Gagnon and Swank (2021) found, professional development (PD) rarely occurred more than once per year, and it did not include recommended attributes, such as coaching, mentoring, and follow up, and was "commonly viewed as ineffective" (p. 149). Furthermore, PD participation rates for mental health-related PD topics were usually provided to only 30%-40% of professionals other than clinical directors and counselors.…”
Section: Staffingmentioning
confidence: 99%